2014
DOI: 10.1007/s00405-014-3397-4
|View full text |Cite
|
Sign up to set email alerts
|

A study of the relationship between the video head impulse test and air calorics

Abstract: The video head impulse test (vHIT) has been proposed as an objective approach to detect peripheral vestibular disorder in a clinical setting. Data from several studies indicate that the vHIT is a useful addition to the vestibular test battery and can give complementary information to caloric testing. This study explores the relationship between lateral canal vestibular occular reflex gain measured using the vHIT system and canal paresis indicated using air calorics in a sample of patients attending a clinic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 21 publications
3
45
0
4
Order By: Relevance
“…The gain is set to 0.79 or greater in normal vestibular function based on 20 published healthy subjects using EyeSeeCam Ò vHIT system [4]. Bell et al redefined the VOR gain normative upper limit 1.21 and lower limit 0.83 of two lateral semicircular canals combined based on 30 asymptomatic healthy subjects using the GN-Otometrics vHIT system [5].…”
Section: Introductionmentioning
confidence: 99%
“…The gain is set to 0.79 or greater in normal vestibular function based on 20 published healthy subjects using EyeSeeCam Ò vHIT system [4]. Bell et al redefined the VOR gain normative upper limit 1.21 and lower limit 0.83 of two lateral semicircular canals combined based on 30 asymptomatic healthy subjects using the GN-Otometrics vHIT system [5].…”
Section: Introductionmentioning
confidence: 99%
“…7 The normal range of the VOR gain parameter in healthy populations has been investigated in many studies and has been found to range between 0.83 and 1.21. 8 Video head impulse test allows the recording of eye movements on a high resolution camera and can even detect covert saccades not visible to the naked eye, thereby providing detailed information about saccades and their features. The advantages of the VHIT test include absence of dizziness and nausea during the evaluation, relatively rapid applicability of the test, assessment of the semicircular canals at high frequencies (5-7 Hz) that simulate everyday rapid head movements, and the opportunity to evaluate all canals separately.…”
Section: Introductionmentioning
confidence: 99%
“…In the event of abnormal VOR function, vHIT identifies both overt and covert corrective reset saccades (i.e., corrective reset saccades that occur after and during the head impulse, respectively), indicating abnormal VOR function and the inability to maintain steady vision during head movement [MacDougall et al, 2009]. Advantages of vHIT over other clinical vestibular measures of canal function (e.g., calorics, rotary chair) are that it provides information regarding individual canal function, is quick to administer, and does not induce dizziness; however, its relationship to other tests of canal function suggest that vHIT is not a replacement to, but adjunctive to other tests of vestibular function [MacDougall et al, 2009;McGarvie et al, 2015a;McCaslin et al, 2014;Bell et al, 2015;McCaslin et al, 2015]. …”
Section: Introductionmentioning
confidence: 99%